A Systematic Review of the Relationship Between Neurodiversity and Psychosexual Functioning in Individuals with Autism Spectrum Disorder (ASD) or Attention-Deficit/Hyperactivity Disorder (ADHD) - Young,Susan; Cocallis,Kelly (Neuropsychiatric Disease and Treatment, 2023)
Susan Young,1,2 Kelly Cocallis3 1Psychology Services Limited, London, UK; 2Department of Psychology, Reykjavik University, Reykjavik, Iceland; 3Health Psychology, Northumbria Healthcare NHS Foundation Trust, Northumberland, UKCorrespondence: Susan Young, Psychology Services Limited, London, UK, Email psychltd@aol.comAbstract: The scientific literature on psychosexual functioning shows a range of outcomes for individuals with neurodiversity. The aim of this article was to synthesize and critically evaluate evidence regarding psychosexual selfhood (orientation), behaviors and experiences in individuals with autism spectrum disorder (ASD) or attention-deficit/hyperactivity disorder (ADHD) to prioritize further research and identify interventions to reduce risk. A systematic review of the literature that compared sexual orientation, behavior and experiences of individuals with ASD or ADHD with those of neurotypical peers was performed in AMED, CINAHL, MEDLINE, PsycARTICLES and PsycINFO, Psychology and Behavioural Sciences Collection, Child Development and Adolescent Studies databases (supplemented by hand-searching of reference lists). Seventeen ASD and nineteen ADHD studies met inclusion criteria. Overall, the studies reviewed suggest poorer psychosexual functioning for individuals with ASD or ADHD compared to neurotypical peers, including a lack of satisfaction in their sexual relationships, sexual dysfunction, risky sexual behaviors, and victimization. This appears to be more marked for females. Individuals with ASD were more likely to identify with a non-heterosexual orientation compared with neurotypical peers. The study identifies gaps in our knowledge relating to risky sexual behaviors (in particular, those relating to sexual health and vulnerability to sexual victimization and perpetration). The public health implications of the findings are discussed. Future research is needed to clarify the mechanisms by which individuals with neurodevelopmental disorders may be at increased risk of adverse psychosexual ...